Predictors of happiness among elderly Malaysians in government-funded care homes - Ghaus, Azmah; Tunku Ahmad, Tunku Badariah; Nordin, Mohamad Sahari; Ismail, Nik Ahmad Hisham (2016)
This study was conducted to explore the predictors of happiness experienced by elderly Malaysians residing in government-funded, long-term care facilities in West Malaysia. Seven dimensions of elderly happiness extracted from an exploratory factor analysis procedure, namely spiritual well-being (SWB), physical well-being (PWB), quality care (QC), social well-being (SWB), contact with nature (CWN), recreation (REC), and empowerment (EMP), were proposed as the likely predictors. The sample comprised 323 senior citizens with a composition of 64% Malay and 68% Muslim. They were purposively selected from nine Rumah Seri Kenangan in eight West Malaysian states and averaged 68 years of age. Enumerators were employed to administer a 57-item elderly happiness scale on the sample. Multiple regression analysis (MRA) was applied on the data with the seven underlying dimensions treated as the predictor variables and extent of happiness as the criterion variable. The regression analysis reveals that the predicted model accounted for 14.93% of the variance in elderly happiness with a standard error of 5.41. As suggested by the ANOVA results, the overall strength of the relationship between the predictors and elderly happiness was statistically significant [F (7, 315) = 9.076, p = .001, Adj. R2 = 14.93]. The criterion variable (extent of elderly happiness) was significantly predicted by three of the seven dimensions, namely social well-being (Beta = .268, t = 3.955, p = .001), recreation activities organized by/at the RSK (Beta = .167, t = 2.620, p = .009), and the RSK’s quality care (Beta = .162, t = 2.522, p = .012). Based on the beta weight, social well-being is the strongest predictor of elderly happiness, followed by recreation and quality care. The results inform the RSKS about aspects they should take care of in ascertaining the overall happiness and well-being of their residents. 57